Analisis Kepedulian Siswa terhadap Perundungan di Sekolah Menengah atas Negeri 2 Dolok Sanggul - Nazla Soraya; Nasywa Shalihah; Yessicha R.C Nainggolan; Amira Awra Basasa Nasution (Departement of Mathematics Education, 2024)
The research aims to determine the meaning, impact, distribution and ways to overcome bullying. The research uses a literature study approach regarding basic theory, impacts, distribution and ways to overcome bullying. This research uses quantitative descriptive methods with the aim of measuring students' level of concern about bullying at school. The research design used was a survey by distributing questionnaires as the main instrument for data collection. The research subjects consisted of 142 students at state high school 2 dolok sanggul, selected randomly to get a good representation of the population. According to the results of the questionnaire distributed by the researchers, a large number of students, namely 51.4%, had never witnessed bullying behavior at school, which suggests that bullying may not be a widespread issue at this school. However, 48.6% of students had seen or experienced bullying, which suggests that there may be some problems with bullying in schools. The phenomenon of bullying between students really needs further attention. Based on the reasons why the perpetrator carried out the bullying action, whether there was a problem between the perpetrator and the victim so that it could not be resolved properly, or whether it occurred because of the perpetrator's environmental factors which made the bullying behavior stick within the perpetrator himself.